Thermodynamic analysis of the performance of a hybrid system consisting of steam turbine, gas turbine and solid oxide fuel cell (SOFC-GT-ST). (1st June 2020) - Pirkandi, Jamasb; Penhani, Hossein; Maroufi, Arman
Highlights: A hybrid system consisting of steam turbine, gas turbine and solid oxide fuel cell (SOFC) is proposed. 9 different steam cycle configurations have been examined. The hybrid cycle effects, efficiency and power outputs are investigated. By adding steam turbines to the cycle the efficiency increases about 15%. Abstract: The main objective of this paper is to model and analyze the thermodynamic performance of a hybrid system consisting of steam turbine (ST), gas turbine (GT) and solid oxide fuel cell (SOFC). What separates this hybrid system from the other existing cycles is the simultaneous use of three modern technologies in a single power generation cycle. In this work, first, 9 different steam cycle configurations have been examined and the best cycle in terms of thermodynamic performance has been selected. The fuel cell used in the hybrid cycle has been analyzed from thermodynamic, thermal and electrochemical standpoints; and, contrary to most previous research works, the operating temperatures of the fuel cell under different working conditions have been determined. The obtained results for the triple hybrid cycle indicate that by adding the steam cycle to the double cycle of gas turbine-fuel cell, the net power generated by the triple system goes up 200% relative to the simple gas turbine cycle and 15% relative to the hybrid cycle of gas turbine-fuel cell. Results also show that the triple hybrid system (with an efficiency of 52%) has a better performance than the hybrid system of gas turbine-fuel cell (with an efficiency of 45.21%) and the simple gas turbine cycle (with an efficiency of 25%).